Undead and undermined - Davidson, MaryJanice (New York : Berkley Sensation, 2011)
Vampire Queen Betsy Taylor thought she couldn't die. So what's she doing in the morgue? It could have something to do with a time-traveling trip she made, and a foe with a wicked agenda that could finally be the real death of Betsy--if she's not careful.
Keywords: Vampires -- Fiction; Taylor, Betsy (Fictitious character) -- Fiction; Sinclair, Eric (Fictitious character) -- Fiction